Effectiveness of prison work programs: Examples of certain programs in the USA - Petrović Vera; Jovanić Goran; Luković Milica (Specijalna Edukacija i Rehabilitacija, 2017)
Punishment or a change with punishment has been an everlasting dilemma of the creators of punishing policy, especially within the prison system. Since perpetrators of serious and dangerous criminal offenses, who according to the degree of risk could not be sentenced to non-institutional penalties, usually serve a prison sentence, there is resistance to shifting the focus of punishment toward correction. Imprisonment is focused more on segregation and isolation, while it is much less invested in rehabilitation programs. The severity of an offence combined with antisocial characteristics of the convicts, increases the need for keeping order, which leaves less room for the implementation of professional training. Work engagement and training reflect the ideas that convicts should be sanctioned for the damage done and for opposing societal norms, but at the same time their future life after being released, their survival and existence by doing legal jobs, should be considered, so that they do not commit new crimes and return to prison. The aim of this paper is to describe the development and application of prison work programs in the USA. It has been shown that there is no general agreement at the conceptual level, at the level of competition in the free market of goods and services, as well as with regard to real effects such engagement of imprisoned convicts actually produces, and to what extent it influences the reduction of recidivism. However, existence and modernization of work programs in prison lead to the conclusion on their usefulness, positive economic effects, and their influence on the reduction of recidivism, despite criticism on various grounds.